Tranexamic Acid to Reduce Postpartum Hemorrhage: A MANDATE Systematic Review and Analyses of Impact on Maternal Mortality - McClure, Elizabeth M.; Jones, Bonnie; Rouse, Doris J.; Griffin, Jennifer B.; Kamath-Rayne, Beena D.; Downs, Allan; Goldenberg, Robert L. (American Journal of Perinatology, 2015)
Objective Postpartum hemorrhage (PPH) is a major cause of maternal mortality, with almost 300,000 cases and ∼72,000 PPH deaths annually in sub-Saharan Africa. Novel prevention methods practical in community settings are required. Tranexamic acid, a drug to reduce bleeding during surgical cases including postpartum bleeding, is potentially suitable for community settings. Thus, we sought to determine the impact of tranexamic acid on PPH-related maternal mortality in sub-Saharan Africa.Study Design We created a mathematical model to determine the impact of interventions on PPH-related maternal mortality. The model was populated with baseline birth rates and mortality estimates based on a review of current interventions for PPH in sub-Saharan Africa. Based on a systematic review of literature on tranexamic acid, we assumed 30% efficacy of tranexamic acid to reduce PPH; the model assessed prophylactic and treatment tranexamic acid use, for deliveries at homes, clinics, and hospitals.Results With tranexamic acid only in the hospitals, less than 2% of the PPH mortality would be reduced. However, if tranexamic acid were available in the home and clinic settings for PPH prophylaxis and treatment, a nearly 30% reduction (nearly 22,000 deaths per year) in PPH mortality is possible.Conclusion These analyses point to the importance of preventive and treatment interventions compatible with home and clinic use, especially for sub-Saharan Africa, where the majority of births occur at home or community health clinics. Given its feasibility to be given in the home, tranexamic acid has potential to save many lives.
Keywords: postpartum hemorrhage; tranexamic acid; maternal mortality; sub-Saharan Africa